2005
DOI: 10.1517/13543784.14.3.223
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of pharmacology and potential anti-obesity properties of H3receptor antagonists/inverse agonists

Abstract: Histamine is a key neurotransmitter that alters central nervous system functions in both behavioural and homeostatic contexts through its actions on the histamine (H) subreceptors H(1), H(2) and H(3) G-protein-coupled receptors. H(3)receptors have a diverse central nervous system distribution where they function as both homo- and hetero-receptors to modulate the synthesis and/or release of several neurotransmitters. H(3) receptors are constitutively active, which implies that antagonists of H(3) receptors may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 99 publications
0
45
0
Order By: Relevance
“…This protective effect has recently been demonstrated in a rat SC injury model, where the administration of H 3 R selective agonist ␣-methylhistamine ameliorated signs of injury including edema formation and blood SC barrier permeability (44). The EAE-protective nature of H 3 R, and the mapping of an EAE-modifying locus controlling disease severity and associated weight loss (Eae8) to the genomic interval containing Hrh3 (24,(28)(29)(30), combined with the known role of H 3 R in weight control (31), all provide evidence that Hrh3 is a good candidate gene for Eae8.…”
Section: Discussionmentioning
confidence: 99%
“…This protective effect has recently been demonstrated in a rat SC injury model, where the administration of H 3 R selective agonist ␣-methylhistamine ameliorated signs of injury including edema formation and blood SC barrier permeability (44). The EAE-protective nature of H 3 R, and the mapping of an EAE-modifying locus controlling disease severity and associated weight loss (Eae8) to the genomic interval containing Hrh3 (24,(28)(29)(30), combined with the known role of H 3 R in weight control (31), all provide evidence that Hrh3 is a good candidate gene for Eae8.…”
Section: Discussionmentioning
confidence: 99%
“…[3] The histamine H 3 receptor is an important G protein-coupled receptor, identified in 1983 by Arrang et. al [4] and cloned and characterized in 1999.…”
Section: Introductionmentioning
confidence: 99%
“…They are predominantly expressed in the brain, where they negatively regulate histamine release, acting as presynaptic autoreceptors (10). Therefore, the therapeutic potential of H3R antagonists͞ inverse agonists for treating obesity has been extensively discussed (12,13). Our previous study using H3R-deficient (H3RKO) mice demonstrated a crucial role for H3Rs in appetite and body-weight regulation (14).…”
mentioning
confidence: 99%
“…However, enhanced histamine release was accompanied by obese and hyperphagia phenotypes in H3RKO mice. Moreover, the effects of pharmacological blockade of H3Rs on appetite and energy homeostasis have remained controversial (6,13,(15)(16)(17)(18)(19).…”
mentioning
confidence: 99%